Medicinal plants and their traditional uses in Thana Village, District Malakand, Khyber Pakhtunkhwa, Pakistan - Gulzar, Haseena; Hazrat, Ali; Gulzar, Kiran; Ali, Fayaz; Khan, Nasrullah; Mohammad Nisar; Khan, Imran; Abid Ullah (International Journal of Endorsing Health Science Research, 2019)
Background: Local herbalists share valuable contribution in usages of plants for different medicinal purposes. The field of ethnobotany plays a key role for modern medicines. Due to the rapid advancement of medical sciences, the use of plant species in traditional ways is getting declining. Documentation of such knowledge was much more necessary for awareness of the local community. Current research was conducted in the village Thana, district Malakand. Methodology: An ethnobotanical survey was conducted through an open-ended and semi-structured questionnaire. The questionnaire collected information about plant species, its therapeutic uses and data about the customary values of these species. Mostly people belonging to rural areas and of more than 40 years of age were interviewed due to their vast experience and knowledge. Several informants were interviewed to confirm information regarding the uses of each plant species. These plants were taken to the local hakims and pansaris additionally. In the majority of cases, single plant species were found to be used in several ways and therefore can be said having numerous roles. Results: On the basis of collected data a total of 50 plant species were documented in the area which plays a key role in improving the health and wealth of local inhabitants. Lamiaceae is being ranked on the top as it contributes number to collected species. Out of 50 plant species,46 species were recorded best for medicinal purposes, 10 plant species were found good as fodder, 4 species for ornamental purposes, 14as food and vegetable, 12 as firewood, 8 for furniture and hedges purposes, 3 species were documented as poisonous and 4 species were found to be utilized for ornamental purpose. Conclusion: The study area is found rich in terms of floral diversity. Local inhabitants of the area use the plant species in traditional ways for the curving of different diseases since early times. Due to anthropogenic pressure and natural disasters flora of the area facing huge pressure of extinction.